A highly active nanostructured metallic oxide cathode for aprotic Li–O2 batteries1. Issue 4 (1st April 2015) - Kundu, Dipan; Black, Robert; Berg, Erik Jämstorp; Nazar, Linda F.
<x xml:space="preserve">Abstract</x> A new nanostructured metallic metal oxide shows excellent ORR/OER properties in a Li–air cell, and highlights the importance of controlling the cathode interface to achieve better Li–O2 cell round-trip efficiency.